Perinatal and neonatal outcome in meconium stained amniotic fluid - Qadir, Shazia; Jan, Sami; Chachoo, Javaid A; Parveen, Shameem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Meconium passage in new born is a developmentally programmed event normally occurring within the first 24 to 48 hours after birth. Intrauterine meconium passage in near-term or term fetuses has been associated with fetomaternal stress factor like hypoxia and infection independent of fetal maturity. The incidence of meconium stained amniotic fluid is 1-18%. The objective of this study was to correlate the presence of meconium in amniotic fluid with perinatal outcome. Methods: A total of 300 women were taken in the study, out of which 54 cases who were found to have meconium on spontaneous or artificial rupture of membranes were monitored with fetal heart rate abnormalities, 5 minute APGAR score and neonatal complications as outcome variables. Results: The incidence of meconium stained liquor was 18%.Fetal heart rate abnormalities were seen more often with thick meconium (62.5%) than with thin meconium (15.8%) which was statistically significant. In the present study there was a good correlation between APGAR score and MAS, 3 neonates with thick meconium in the severely asphyxiated group had MAS. No babies with APGAR >7 had MAS. Neonatal morbidity due to MAS was seen in 3 (18.8%) cases and mortality was seen in 4 (7.41%) cases. Conclusions: The significance of meconium in amniotic fluid is a widely debated subject. Traditionally meconium has been considered as a sign of fetal distress occurring due to hypoxia. However it is now recognized as a manifestation of a normally maturing gastrointestinal tract. In a global sense it is still considered a marker for adverse perinatal outcomes. The presence of thick meconium is associated with increase in the perinatal morbidity and mortality and hence its presence should not be overlooked.